Heat Stress Altered the Vaginal Microbiome and Metabolome in Rabbits - Shi, Yu; Tang, Lipeng; Bai, Xue; Du, Kun; Wang, Haoding; Jia, Xianbo; Lai, Songjia (Frontiers in Microbiology, 2022)
Heat stress can have an impact on parental gamete maturation and reproduction functions. According to current research, the microbial composition of the vaginal cavity is species specific. Pregnancy, menstruation, and genital diseases have been linked to the dynamics of vaginal ecology. In this study, we characterized the vaginal microbiota and metabolites after heat stress. At the phylum level, the rabbit’s vaginal microbial composition of rabbit showed high similarity with that of humans. In the Heat group, the relative abundance of the dominant microbiota Actinobacteria, Bacteroidetes, and Proteobacteria increased, while the relative abundance of Firmicutes decreased. Furthermore, heat stress significantly increased the relative abundance of W5053, Helcococcus, Thiopseudomonas, ldiomaarina, atopostipes, and facklamia, whereas the relative abundance of 12 genera significantly decreased, including Streptococcus, UCG-005, Alistipes, [Eubacterium]_xylanophilum_group, Comamonas, RB41, Fastidiosipila, Intestinimonas, Arthrobacter, Lactobacillus, Leucobacter, and Family_xlll_AD3011_group. Besides, the relative concentrations of 158 metabolites differed significantly between the Heat and Control groups. Among them, the endocrine hormone estradiol (E2) increased in the Heat group and was positively associated with a number of metabolites such as linolelaidic acid (C18:2N6T), N-acetylsphingosine, N-oleoyl glycine, trans-petroselinic acid, syringic acid, 2-(1-adamantyl)-1-morpholinoethan-1-one, 5-OxoETE, and 16-heptadecyne-1,2,4-triol. Further, the majority of the differential metabolites were enriched in steroid biosynthesis and endocrine and other factor-regulated calcium reabsorption pathways, reflecting that heat stress may affect calcium metabolism, hormone-induced signaling, and endocrine balance of vaginal ecology. These findings provide a comprehensive depiction of rabbit vaginal ecology and reveal the effects of heat stress on the vagina via the analysis of vaginal microbiome and metabolome, which may provide a new thought for low female fertility under heat stress.